Sendang Sayuti Melik sebagai Potensi Objek Wisata Kadilobo: Kajian Sastra Lisan - Ocviliana, Linda (Universitas Lampung, 2023)
Each region always has a variety of oral literature that is different, both in characteristics and uniqueness that holds a variety of potential as a tourist attraction that is worth developing. This research examines the tourism potential of Sendang Sayuti Melik. The purpose of this research is to find out what stories are contained in the Sendang Sayuti Melik to find out how the community's efforts in developing the tourism potential that exists in Kadilobo village. This research is descriptive qualitative. Then, the methods used in this research consist of data collection methods and data analysis methods. The results showed that the community's efforts in developing the tourism potential that exists in the spring are planning to make a monument to Sayuti Melik located next to the village. However, in line with Community Based Tourism, namely efforts to develop a community-based tourism object, it is necessary to apply several principles such as including community members in starting every aspect, developing the quality of life of the community, maintaining the uniqueness of character and culture in the local area, helping the development of learning about cultural exchange in the community. These principles are to create community-based tourism management, namely the natural resources in Kadilobo village. The effort to develop the potential contained in the spring in the hope that the outside community can know and recognize the existence of the Sendang in Kadilobo village.Keywords: oral literature, sendang, sayuti melik, kadilobo